Utilising the Antimicrobial Resistance Index to Identify Multidrug Resistance Profiles of Priority Pathogens: A Case Study from Central Tanzania (Tanzania Medical Journal, 2025)
Background: Antimicrobial stewardship (AMS) programs have implemented various surveillance interventions, such as profiling bacterial resistance patterns and developing economic cases for effective management. However, there has been comparatively less focus on evaluating the Drug Resistance Index (DRI). The DRI serves as a crucial instrument for evaluating the efficacy of antimicrobial therapies and examining the patterns of bacterial resistance. Evaluating the efficacy of antibiotics and effectively communicating the issue of antimicrobial resistance are crucial components in developing AMS programs within hospital environments.Objective: This study utilised the DRI to analyse the distribution of multidrug-resistant organisms (MDROs) associated with widely prescribed antimicrobials at Benjamin Mkapa Hospital (BMH), focusing on their application in treating both Gram-positive and Gram-negative infections.Methods: A retrospective descriptive study was conducted using combined data on total bacterial isolates, resistance isolates, and antibiotic usage to calculate the DRI over the years 2020, 2021, and 2022.Results: The three-year DRI for the priority pathogens Escherichia coli and Klebsiella pneumoniae isolated from urine samples is 46%. The average three-year DRIs for pathogens isolated from blood samples were as follows: Acinetobacter baumannii (37%), Escherichia coli (65%), Klebsiella pneumoniae (62%), Streptococcus pneumoniae (60%), and Staphylococcus aureus (63%). Additionally, the DRIs for bacteria isolated from pus and wound swabs were: Acinetobacter baumannii (60%), Escherichia coli (57%), Klebsiella pneumoniae (66%), Pseudomonas aeruginosa (34%) and Staphylococcus aureus (75%).Conclusion: All evaluated priority pathogens displayed multidrug resistance, with DRI values surpassing 25%, a clear indicator of escalating antimicrobial resistance (AMR). These findings underscore the necessity for robust antibiotic stewardship programs within healthcare institutions, alongside the regular dissemination of antibiotic consumption data to the BMH. Additionally, the formulation of comprehensive policies and treatment guidelines is essential to regulate antibiotic prescriptions effectively, thereby preserving their long-term efficacy. These initiatives are pivotal in the fight against AMR, facilitating the restoration of antimicrobial susceptibility and mitigating the DRI.